PRICING STRATEGY IN THE INDONESIAN CONSTRUCTION INDUSTRY - Krishna Mochtar (Civil Engineering Dimension, 2002)
Issues related to pricing strategy in the Indonesian construction industry are covered%2C including problems of current pricing strategy in construction%2C exploration of pricing strategies with a market-based approach%2C and survey findings of the top Indonesian contractors regarding their current pricing practices and the applicability of market-based pricing strategy models developed by Mochtar and Arditi. Comparisons with similar survey findings of the top U.S. contractors are conducted whenever possible. In conclusion%2C the belief that current pricing strategy in construction is predominantly cost-based is confirmed by the survey findings%3B indeed%2C in setting the markup%2C most contractors rely on subjective assessment of the competition. Using simulated bidding scenarios%2C it is discovered that Indonesian contractors tend to be more market-based as they know more about the owner%5C%27s characteristics%2C competitors%5C%27 characteristics%2C and market demand. Consequently%2C the implementation of bidding procedure proposed by Mochtar and Arditi is supported. To maximize the benefits of market-based pricing strategies%2C the bidding procedure change should be explored by all parties involved in the Indonesian construction industry. Abstract in Bahasa Indonesia : Cost-based+pricing%2C+market-based+pricing%2C+pricing+variables%2C+bidding+procedure.